Pengembangan Bahan Ajar menggunakan Genially pada Materi Lingkungan Kita Sedang Terancam untuk Meningkatkan Minat Belajar Peserta Didik - Rahma Hesti Fauziah; Nandang Hidayat; Dadang Jaenudin (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Science learning in elementary schools still uses conventional teaching materials that are less interactive, so that students' learning interest has not developed optimally. This study aims to develop Genially-based teaching materials on the topic of our environment being threatened, assess its feasibility and practicality, and describe its effectiveness in increasing learning interest. The study used the Research and Development method with the ADDIE model. The trial subjects included 5 students in the limited test, 33 students in the broad test and effectiveness test, and 3 teachers. Data were collected through validation by material experts, language, media, teacher and student response questionnaires, and learning interest questionnaires. The final validation results obtained a score of 75 from the lecturer material expert, 70 from the teacher material expert, 75 from the language expert, and 69 from the media expert, all categorized as very feasible. Practicality obtained an average score of 48 in the limited test, 46 in the broad test, and 47 from teacher responses, all categorized as very practical. The average learning interest increased from 74 in the moderate category to 101 in the very high category. Genially's teaching materials are assessed as being appropriate, practical, and descriptively effective in increasing the learning interest of fourth grade students.